The M. tuberculosis Rv1523 Methyltransferase Promotes Drug Resistance Through Methylation-Mediated Cell Wall Remodeling and Modulates Macrophages Immune Responses - Ali, Sabeeha; Ehtram, Aquib; Arora, Naresh; Manjunath, P.; Roy, Deodutta; Ehtesham, Nasreen Z.; Hasnain, Seyed E. (Frontiers in Cellular and Infection Microbiology, 2021)
The acquisition of antibiotics resistance is a major clinical challenge limiting the effective prevention and treatment of the deadliest human infectious disease tuberculosis. The molecular mechanisms by which initially Mycobacterium tuberculosis (M.tb) develop drug resistance remain poorly understood. In this study, we report the novel role of M.tb Rv1523 MTase in the methylation of mycobacterial cell envelope lipids and possible mechanism of its contribution in the virulence and drug resistance. Initial interactome analyses predicted association of Rv1523 with proteins related to fatty acid biosynthetic pathways. This promoted us to investigate methylation activity of Rv1523 using cell wall fatty acids or lipids as a substrate. Rv1523 catalyzed the transfer of methyl group from SAM to the cell wall components of mycobacterium. To investigate further the in vivo methylating role of Rv1523, we generated a recombinant Mycobacterium smegmatis strain that expressed the Rv1523 gene. The M. smegmatis strain expressing Rv1523 exhibited altered cell wall lipid composition, leading to an increased survival under surface stress, acidic condition and resistance to antibiotics. Macrophages infected with recombinant M. smegmatis induced necrotic cell death and modulated the host immune responses. In summary, these findings reveal a hitherto unknown role of Rv1523 encoded MTase in cell wall remodeling and modulation of immune responses. Functional gain of mycolic acid Rv1523 methyltransferase induced virulence and resistance to antibiotics in M. smegmatis. Thus, mycolic acid methyltransferase may serve as an excellent target for the discovery and development of novel anti-TB agents.